Isolation and determination of Acanthamoeba genotypes in surface water of Ilam city - Azadeh Ghadesi; Hamid Hasanpour; Razi Naserifar; Jahangir Abdi; Mohammad Reza Mahmoudi; Habibollah Turki; Omid Raiesi; Muhammad Ibrahim Getso; Asad Mirzaei (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Acanthamoeba, a widely distributed free-living amoeba with 20 genotypes identified through rRNA gene sequencing, exhibits varying degrees of pathogenicity influenced by its genotype. This study focuses on assessing the prevalence of Acanthamoeba species in the surface waters of Ilam, located in western Iran, utilizing morphological analysis and sequencing of the 18S rRNA gene through the PCR method. A total of 50 water samples were collected from various regions within Ilam city, situated in the southwest of Iran. To isolate Acanthamoeba parasites from the samples, a culture method was used, and all utilized culture media were scrutinized through microscopic and molecular techniques. The parasite’s genotype was determined by sequencing a 500-bp fragment of the 18S rRNA gene. Using microscopic and molecular methods, 19 and 16 water samples tested positive, respectively. The 18S rRNA sequences revealed that the isolates belonged to the T4, T2, and T11 genotypes. This study emphasizes the presence and inclination for close contact with highly pathogenic genotypes of Acanthamoeba in the surface waters of Ilam City.